2017
DOI: 10.1111/jcpp.12815
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid symptoms of inattention, autism, and executive cognition in youth with putative genetic risk

Abstract: Comorbid symptoms of ASD, IA, and cognitive deficits are likely influenced by common neurogenetic factors. Known genetic risk in ASD may inform future investigation of putative genetic causes of IA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The presence of nonadditive patterns points to unique processing or additional factors underlying the cognitive performance in comorbid patients. Previous studies found that co-occurring symptoms of ASD and ADHD are explained by not only overlapping genetic factors of the pure disorders (Arnett et al, 2018) but also distinct gene-environmental influences (Kröger et al, 2011; Rommelse et al, 2010; Ronald, Simonoff, Kuntsi, Asherson, & Plomin, 2008). More research is warranted to better understand the status of comorbid ADHD and ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of nonadditive patterns points to unique processing or additional factors underlying the cognitive performance in comorbid patients. Previous studies found that co-occurring symptoms of ASD and ADHD are explained by not only overlapping genetic factors of the pure disorders (Arnett et al, 2018) but also distinct gene-environmental influences (Kröger et al, 2011; Rommelse et al, 2010; Ronald, Simonoff, Kuntsi, Asherson, & Plomin, 2008). More research is warranted to better understand the status of comorbid ADHD and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that co-occurring symptoms of ASD and ADHD are explained by overlapping genetic factors of the pure disorders (Arnett et al, 2017) but also distinct gene-environmental influences (Ronald et al, 2008;Rommelse, Franke et al, 2010;Kröger et al, 2011). More research is warranted to better understand the status of comorbid ADHD and ASD.…”
Section: 4mentioning
confidence: 99%
“…High levels of hyperactive/impulsive behaviour are common in children with learning‐related difficulties (Hawkins, Gathercole, Astle, The Calm, & Holmes, 2016); indeed, in some cases elevated inattention can be as common as in children with ADHD (Bathelt et al., 2018; Holmes et al., 2014; Willcutt, Pennington, Olson, & DeFries, 2007). In addition, both hyperactive / impulsive behaviours and inattention are common in autistic children (Arnett et al., 2018; van Steijn et al., 2012). Taxometry provides further evidence that both kinds of behaviour are distributed continuously across the population as a whole (Marcus & Barry, 2011).…”
Section: New Transdiagnostic Approachesmentioning
confidence: 99%
“…ASD starts in early childhood around the age of 3 years and persists throughout life [ 79 ]. People with ASD commonly experience other comorbidities such as memory and learning deficits, seizures, motor incoordination, changes in sensory perception, anxiety, and sleep disturbances [ 80 82 ]. According to the data released by the Centers for Disease Control and Prevention (CDC) and Autism and Developmental Disabilities Monitoring network, about 1 in 44 (2.3%) children in the United States have been identified with autism in 2018 [ 83 ].…”
Section: Circadian Dysfunction Mtor and Asdmentioning
confidence: 99%